Exploring the causal link between childhood maltreatment and asthma: a Mendelian randomization study - Zheng Zhang; Yating Wang; Jiazheng Li; Hao Ren; Xinglian Wang; Haitang Qiu; Huirong Luo; Xueqian Wang; Junyao Li; Renqin Hu; Yanwei Guo; Jinglan Tan; et al. (European Journal of Psychotraumatology)
Background: Prior research indicates a potential connection between childhood maltreatment and asthma. In response, we designed a Mendelian Randomization (MR) study to further investigate this association.Methods: Utilizing the MR approach, we leveraged Genome-Wide Association Studies (GWAS) data from the UK Biobank (UKB). Our primary outcome was asthma, analyzed through GWAS datasets termed AsthmaUKB and AsthmaIEU, sourced from two distinct studies. Additionally, we conducted stratified analyses focusing on pediatric asthma and adult asthma to address different asthma phenotypes. The causal impact of childhood maltreatment (CM) on asthma was assessed using inverse-variance weighted (IVW) methods, MR-Egger, and MR-PRESSO tests, thereby enhancing the robustness and generalizability of our findings.Results: The IVW analyses identified significant associations between CM and increased risks for AsthmaUKB (OR = 1.59, 95% CI = 1.23–2.05, p < .001), AsthmaIEU (OR = 1.04, 95% CI = 1.02–1.06, p < .001), pediatric asthma (OR = 1.72, 95% CI = 1.26–2.35, p = .001), and adult asthma (OR = 1.71, 95% CI = 1.17–2.48, p = .005). The MR-Egger and MR-PRESSO results confirmed the absence of pleiotropy, reinforcing our causal inferences. Although Cochran’s Q test indicated some heterogeneity among asthma subtypes (p > .05), the robustness of the IVW results remains reliable.Conclusions: Our findings suggest a potential causal relationship between CM and various asthma phenotypes, as validated through rigorous Mendelian randomization analyses. These results emphasize the importance of considering CM in asthma prevention and intervention strategies and lay the groundwork for further investigation into how early-life adversities may predispose individuals to asthma, contributing to a deeper understanding of its etiological pathways.